From Oral Tradition to Written Text: Neuwirth’s Insights on the Spoken Aspects of the Qur’an - Ihwan Agustono (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
This article analyzes the oral and written aspects of the Qur’an through Angelika Neuwirth’s pre-canonical framework, using sūrah al-Ikhlāṣ as a case study. It highlights Neuwirth’s argument that the oral nature of the Qur’an is essential for understanding its original communicative context, which has been obscured by its textual codification. The study employs a historical-critical methodology to examine the sociolinguistic context and the dynamic oral features of the Qur’an prior to its codification. Drawing on Neuwirth’s foundational works and supported by secondary literature, it proposes a pre-canonical reading approach that seeks to recover the socio-historical dimensions often overlooked in canonical interpretations. By exploring the interplay between oral and written dimensions, this study reveals how sūrah al-Ikhlāṣ reflects its early reception and positions it within its historical and cultural context. It addresses the broader question of how pre-canonical approaches enhance understanding of the Qur’an’s formative period. The findings underscore the layered meanings and contextual aspect embedded in the text which demonstrates the potential of pre-canonical readings to uncover the Qur’an’s historical and communicative complexities.